2019
DOI: 10.19044/esj.2019.v15n15p244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reactor Temperature on Pyrolysis of Lignocellulosic Medical Waste in a Fixed Bed Reactor

Abstract: The lethargic modes of medical waste disposal in many developing countries have been a cause of concern to many regulatory agencies. In this study, effect of reactor temperature on pyrolysis of lignocellulosic medical waste in a fixed bed reactor was investigated. Gauze bandage was procured from AKOL Pharmacy, Ogbomoso, South-Western Nigeria. Samples of the gauze bandage, 40 g each at a time, were fed into a retort and the retort inserted into a developed fixed bed reactor for pyrolysis at different temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…This reaction scheme depends on the mechanism of the heat and mass transfer between the reactor and the product. The dynamics of heat flux surrounding the wood chips, as heat is transferred from the surface to the core, are related to their shape [18,19]. Investigating some possible shapes of wood chips, the authors of [18,19] showed that the pyrolysis duration and the final mass fraction are shape dependent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This reaction scheme depends on the mechanism of the heat and mass transfer between the reactor and the product. The dynamics of heat flux surrounding the wood chips, as heat is transferred from the surface to the core, are related to their shape [18,19]. Investigating some possible shapes of wood chips, the authors of [18,19] showed that the pyrolysis duration and the final mass fraction are shape dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of heat flux surrounding the wood chips, as heat is transferred from the surface to the core, are related to their shape [18,19]. Investigating some possible shapes of wood chips, the authors of [18,19] showed that the pyrolysis duration and the final mass fraction are shape dependent. The intra-particle structural dynamics of the wood chips are also affected by the shapes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations